PROTOTIPE INTEGRASI DATA MORBIDITAS PASIEN PUSKESMAS KEDALAM DATA WAREHOUSE DI DINAS KESEHATAN KABUTEN BANTUL - Totok - Suprawoto; Enny Itje Sela; Syamsu Windarti (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2017)
Bantul District Health Office (DHO Bantul) is one of the agencies that currently experiencing problems to obtain accurate and current health information. Reports to be made routinely by puskesmas further recapitulated in Bantul Health Office are reports on outpatient morbidity such as the report of Integrated Disease Surveillance (STP), disease report by type, and others.From result of analysis and design of data warehouse based on fact constellation schema which include dimension: time, patient, age group, disease and puskesmas, furthermore can be analyzed further for the purpose of decision making using data mining. Furthermore, it can also be used to analyze patient data from various dimensions (time, patient, age group, illness and puskesmas), and analyze the growth of patient number from each period of time which is useful for the management of DHO Bantul. Successfully built prototype data integration morbidity of outpatient Puskesmas. To ease the burden of the surveillance officer to make a report to DHO Bantul has made the application of Integrated Disease Surveillance (STP). While some types of reports are needed every periodic can be simulated using instaview or pentaho report.